STRUGGLE FOR BEING A FREE MAN IN MARK TWAIN'S THE ADVENTURES OF HUCKLEBERRY FINN: A MARXIST APPROACH - DWI A , LAELA (2007)
This research is paper is primarily intended to identify how the major character struggles for being a free man in Mark Twain's The Adventures of Huckleberry Finn by Marxist Perspective, and to analyze the novel based on its structural elements. In analyzing the novel, the writer uses qualitative study. The data are collected by using library research. The technique of data analysis is descriptive analysis. The research significance is to give contribution to the body of knowledge, particularly the literary study on Mark Twain's The Adventures of Huckleberry Finn. The result of the analysis confirms as follows. First, the novel has close relationship with the social reality of American society in the second half of the nineteenth century. Second, it describes the struggle of the major characters for being free men. Huck and Jim realize their idea to make an action because they are treated despotically by the adult and owner or upper class. This represents Mark Twain's protest against oppression, particularly the practices of slavery in the second half of the 19th century.